2015
DOI: 10.1111/bph.13323
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific action of (Pro3)GIP – a full agonist at human GIP receptors, but a partial agonist and competitive antagonist at rat and mouse GIP receptors

Abstract: Background and PurposeSpecific, high potency receptor antagonists are valuable tools when evaluating animal and human physiology. Within the glucose‐dependent, insulinotropic polypeptide (GIP) system, considerable attention has been given to the presumed GIP receptor antagonist, (Pro3)GIP, and its effect in murine studies. We conducted a pharmacological analysis of this ligand including interspecies differences between the rodent and human GIP system.Experimental ApproachTransiently transfected COS‐7 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 61 publications
3
74
2
2
Order By: Relevance
“…On the human GIP receptor, we observed GIP(6-30)NH 2 to have the lowest affinity of the truncated GIP (1-30)NH 2 variants and poor antagonistic properties. This is not in line with previous studies, but the pharmacological differences between rodent and human GIP systems are not yet clarified (Sparre-Ulrich et al, 2015). In contrast to the findings for GIP(6-30)NH 2 , our results of the human GIP(7-30)NH 2 are in line with previous studies using the porcine GIP(7-30)NH 2 on the rat GIP receptor (Tseng et al, 1996;Gelling et al, 1997;Tseng et al, 1999;Hinke et al, 2001).…”
Section: Figurecontrasting
confidence: 87%
“…On the human GIP receptor, we observed GIP(6-30)NH 2 to have the lowest affinity of the truncated GIP (1-30)NH 2 variants and poor antagonistic properties. This is not in line with previous studies, but the pharmacological differences between rodent and human GIP systems are not yet clarified (Sparre-Ulrich et al, 2015). In contrast to the findings for GIP(6-30)NH 2 , our results of the human GIP(7-30)NH 2 are in line with previous studies using the porcine GIP(7-30)NH 2 on the rat GIP receptor (Tseng et al, 1996;Gelling et al, 1997;Tseng et al, 1999;Hinke et al, 2001).…”
Section: Figurecontrasting
confidence: 87%
“…Such a scenario is highly unlikely, however, as our data shows that the GLP-1R-overexpressing SH-hGLP-1R#9 cell line dramatically enhances the neurotrophic and neuroprotective effects of twincretin. Additionally, although one recent publication suggests that human (Pro3)GIP may actually be a full agonist of the human GIPR, rather than an antagonist (Sparre-Ulrich et al, 2016), several results obtained in the current study (data not shown), in addition to the results displayed in Fig. 1c, suggest that (Pro3)GIP is in fact an antagonist of the human GIPR.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly to the present study, a statistically significant difference was only found vs mono‐GIP receptor agonist treatment. It is not yet clear whether this presumably enhanced effect of combined GIP receptor and GLP‐1 receptor activation can be translated to human diabetes, particularly because of species differences in GIP sensitivity and species differences at the GIP receptor level . An additive insulinotropic effect has been demonstrated in an infusion study in healthy participants, but not in patients with T2DM .…”
Section: Discussionmentioning
confidence: 99%